How Technology Readiness Shapes Facial Recognition Payment Adoption: An Integrated Structural Model of Cognitive, Trust, and Risk Beliefs - Cheng, Yue; Mohammad, Jihad (International Review of Management and Marketing, 2026)
Facial recognition payments are gaining widespread adoption, yet the psychological underpinnings of their acceptance remain unclear. This study introduces technological readiness as a second-order formative construct to explain how users’ latent attitudes influence their perceptions of usability, usefulness, trust, and risk toward facial recognition payment systems. Data from 398 participants were analyzed using partial least squares structural equation modeling. Results indicate that this second-order construct significantly influences all perceived beliefs, highlighting its central role in user evaluations. Usability, trust, and perceived risk emerge as strong predictors of usage intention, while perceived ease of use exerts an indirect effect. Importance-performance analysis underscores that enhancing usability and trust should be strategic priorities for boosting user adoption. This study enriches theoretical understanding of biometric payment acceptance and provides practical guidance for improving system design and user communication.